Legal Protection for Debtors in the Pre-Project System of Sale of Credit Agreements Ownership of Apartments - Disty, Nafsi Khotimah; Surahmad, Surahmad (Jurnal Ius Constituendum, 2024)
This research aims to find out the validity of the apartment ownership credit agreement (KPA) with PPJB as collateral and legal protection for debtors if the developer of the pre-project selling system defaults. This research is motivated by cases of developers of pre-project selling systems that default and cause losses to consumers who have been bound in KPA with the bank. This research is needed because there are no regulations governing PPJB as collateral and there is an imbalance of power between the debtor and the creditor because of a standard agreement. The discussion on this topic has not been comprehensively explained in previous studies. This research uses normative legal research with a statutory approach with data collection techniques in the form of a literature study. The results show that PPJB as collateral is not ideal, but it does not affect the validity of the KPA agreement. Then, in terms of legal protection for debtors who are harmed by developers, they can refer to Law 8 of 1999 concerning Consumer Protection because the position of debtors is equated with consumers.